MANGROVE HEALTH ANALYSIS USING HEMISPHERICAL PHOTOGRAPHY METHOD IN SUNGAI GUNTUNG WATERS OF KATEMAN DISTRICT INDRAGIRI HILIR REGENCY RIAU PROVINCE - Muhammad, Andi Syahroni; Mulyadi, Aras; Siregar, Sofyan Husein (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Along the river and coastal waters of the Sungai Guntung of Kateman District Indragiri Hilir Regency Riau Province covered with mangroves forreduceswell wind, seawave, and sea water intrusion. There is potential destruction to mangrove in the Sungai Guntung such as industrial activities and use of mangrove stems for building foundation materials. The purpose of this researchis determine the type of mangroves dominate and determine the health of mangroves using hemispherical photgraphy method and line transect plot method. The survey was conducted from July 2019 in the Sungai Guntung of Indragiri Hilir district by determining the station with purposive sampling, station 1around the settlement, station 2 at the estuary far from the settlement, and station 3 around the industry. The results of this study indicate there are 11 types of mangroves from 5 different families dominated by R. apiculata mangrove species, mangrove health in the Sungai Guntung is still in good condition, station 1 canopy closure 79,56% with density 1.456 trees/ha, station 2 canopy closure 81,92% with density 1.622 trees/ha, and station 3 canopy closure 75,73% with density 1.122trees/ha. Kata kunci : Mangrove,Dominance, Density, Canopy cover, Hemispherichalphotography.